Balcony design parameters on passive design strategy / Fatin Nursyafiqah Khairul Anuar, Asniza Hamimi Abdul Tharim and Wan Samsul Zamani Wan Hamdan - Khairul Anuar, Fatin Nursyafiqah; Abdul Tharim, Asniza Hamimi; Wan Hamdan, Wan Samsul Zamani (2022)
An ideal form of natural ventilation in the tropics is the cross-ventilation strategy for dense urban areas. However, for a building with a deep layout plan in terrace houses, in particular, a single-sided ventilation strategy is inevitable, resulting in a substantially reduced ventilation efficiency compared to a cross-ventilation strategy. Hence, one of the most desirable architectural features for improving indoor air velocity in space is the implementation of a proper balcony architecture with the aid of a wing wall which acts as an effective façade treatment in enhancing the ventilation flow rate. Studies on how a balcony as a façade treatment influences the performance of indoor natural ventilation are limited in literature, and unlike other openings such as windows, a balcony as a passive ventilation strategy is not adequately explored particularly in double-story terraced houses. The primary aim of this study is to identify the effects of balcony design and its integration with wing walls in a double-storey terrace house, whereas the purpose of this paper is to review numbers of prominent publications in identifying the parameters and variables measured to carry out CFD simulation afterward. Several parameters and variables have been discovered in balcony design as a passive ventilation strategy. Through a Systematic Literature Review (SLR) method, this paper will examine these parameters and variables to propose appropriate wing walls configurations as an effective façade treatment in balcony design for simulation work.